Does the Belt and Road Initiative Promote Bilateral Trade? An Empirical Analysis of China and the Belt and Road Countries. (May 2023) - Fan, Sha
The development of trade is an essential element of the Belt and Road Initiative (BRI) and a significant effort by China to promote inter-regional economic development. Using Chinese trade data from 190 countries and regions worldwide from 1993 to 2021, this article quantitatively analyzes (a) if and to what extent the BRI has promoted bilateral trade development, (b) how trade with China has contributed to the country's economic growth and (c) what commodity and regional heterogeneity exist in these effects. The empirical results show that the BRI significantly increases China's trade with the countries of the Belt and Road Initiative and countries along the Belt and Road route and significantly increases imports and exports in all five commodity categories—primary goods, resource-intensive manufactured goods, low-tech, medium-tech, and high-tech manufactured goods. Meanwhile, the trade volume with China substantially contributes to the economic development of the trading countries. However, Asia, Europe, and Africa show different characteristics in all three aspects mentioned above. These results show that the BRI not only benefits China's international trade but also promotes the trade development of the involved countries. It clarifies the crucial role this open, inclusive inter-regional economic cooperation plays in global trade growth when facing the escalating anti-globalization sentiment.